Reducing concrete permeability by using natural pozzolans and reduced aggregate-to-pasteratio - Fernando Bustos (Journal of Civil Engineering and Management, 2015)
Improved durability of concrete is mainly achieved with low-permeability. Permeability depends on permeability of the bulk cement paste (CP) and that of its interfacial transition zone (ITZ). Even though permeability of CP is well understood and can be adequately controlled, permeability of ITZ is not well understood yet. This paper shows that minimizing permeability of concrete requires minimizing permeability of CP by using a supplementary cementing material (SCM) such as natural pozzolans (NP) and minimizing ITZ by reducing aggregate content until maximum cement content. This was done by comparing performance of concrete made with ordinary Portland cement (OPC) and blended cement (OPC+NP) at the same w/b, and by comparing performance of concrete with different amount of ITZ at the same w/b. All of this was performed through testing of mechanical properties, air permeability, sorptivity, chloride ion diffusion, and aggregate specific surface. Results show that NP reduced air permeability by 84% and chloride ion diffusion by 66%, but increased sorptivity up to 140%. ITZ has an important effect in all properties; especially in air permeability where sensitive reduction of more than a 90% was achieved. ITZ effect seems to be as important as using SCMs in improving durability of concrete.